SUNRISE AND SUNSET EFFECTS ON COSMIC NOISE ABSORPTION ASSOCIATED WITH AURORA AND MAGNETIC STORMS - HULTQVIST,BENGT (1962)
The riometer recordings taken at Kiruna during the period September 1958 through 1961 were investigated with respect to variation of auroraltype absorption during twilight periods. The average A sub D/A sub N ratio, i.e., that between post- and pre-twilight absorption at sunrise, and between pre- and p st-twilight values at sunset, over the entire period has been found to be 1. 1-1. 2. This value is much lower than that which could be expected (about 3) on the basis of the most recently proposed height distributions of lambda = (negative ion density)/(electron density). It is concluded that the lambda distributions should be decreased so that even the night profile of lambda would have the value 1 at an altitude of about 60 kms. (Author)